Ergogenic effects of sodium bicarbonate supplementation on middle-, but not short-distance swimming performance tests: a meta-analysis - Grgic, J. (Journal of Dietary Supplements, 2022)
This meta-analysis explored the effects of sodium bicarbonate supplementation on swimming performance. Seven databases were searched to find relevant studies. A random-effects meta-analysis of standardized mean differences (SMD) was performed to analyze the data. Nine studies were included in the review. There was no significant difference between placebo and sodium bicarbonate when considering data from all included studies (SMD: -0.10; p = 0.208) or in the subgroup analysis for 91.4-m and 100-m swimming tests (SMD: 0.11; p = 0.261). In the subgroup analysis for 200-m and 400-m swimming tests, there was a significant ergogenic effect of sodium bicarbonate (SMD: -0.22; p < 0.001). Overall, these results suggest that sodium bicarbonate ingestion improves performance in 200-m and 400-m swimming events. The ergogenic effects of this supplement were small, but they may also be of substantial practical importance given that placings in swimming competitions are commonly determined by narrow margins.